2005
DOI: 10.1021/ja0515147
|View full text |Cite
|
Sign up to set email alerts
|

Sunfish Cationic Amphiphiles:  Toward an Adaptative Lipoplex Morphology

Abstract: A detailed physicochemical study is presented on a new class of cationic amphiphiles, Sunfish amphiphiles, recently designed, synthesized, and tested for gene delivery. These materials have two hydrophobic tails, connected to the cationic pyridinium headgroup at the 1- and 4-positions. Two extreme morphologies can be visualized, i.e. one by back-folding involving association of both tails at one side of the pyridinium ring and one by independent unfolding of the tails, the two molecular geometries leading to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…In contrast, cationic amphiphiles are often characterized by a packing parameter (relatively small head group area vs relative large hydrocarbon tail area) that leads to the formation of lipoplexes organized in inverted phases [9]. The H II phase has been widely recognized as promoting transfection in vitro [21,36,37,43]; however, as noted, such a colloidal destabilization before reaching the target site could prove disadvantageous, particularly upon their administration in vivo. As lipoplexes with a lamellar organization are less prone to aggregation than lipoplexes that have adopted an inverted hexagonal phase, such a property would preclude them from accumulating in the lungs, as commonly seen for cationic delivery vehicles [15,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cationic amphiphiles are often characterized by a packing parameter (relatively small head group area vs relative large hydrocarbon tail area) that leads to the formation of lipoplexes organized in inverted phases [9]. The H II phase has been widely recognized as promoting transfection in vitro [21,36,37,43]; however, as noted, such a colloidal destabilization before reaching the target site could prove disadvantageous, particularly upon their administration in vivo. As lipoplexes with a lamellar organization are less prone to aggregation than lipoplexes that have adopted an inverted hexagonal phase, such a property would preclude them from accumulating in the lungs, as commonly seen for cationic delivery vehicles [15,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The increase of liposomes resulted in a reduced viability of the cells (Table 1) but did not correlate with transfection efficiency (Table 2) despite positively charged lipoplexes enable efficient binding to the cell surface (Scarzello et al 2005), an overload of lipoplexes enhances the cell-toxicity (Templeton et al 1997). EGFP expression was merely driven by total DNA uptake (Farhood et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It has shown lipoplex size is very important for gene transfer to actively endocytosing cells (Ross & Hui, 1999), as such the influences on transfection efficiency: DNA ratio, types of liposomes, incubation time in polyanion containing media, and time of serum addition, are channeled mostly through their influences on lipoplex size. 3.1 DOPE DOPE often presents a super synergistic effect when used in cationic liposomes, because DOPE destabilized lipid bilayers, and it was believed to be involved in endosomal disruption (Litzinger & Huang, 1992), allowing the release of DNA into the cytosol (Farhood et al, 1995) and leading to mixed bilayers (Scarzello et al, 2005). Most studies have shown that lipoplexes containing the non-bilayer-phase-preferring lipid DOPE or cholesterol would promote H C II organization (Zuhorn et al, 2005).…”
Section: Helper Lipids and Morphology Of Lipoplexesmentioning
confidence: 99%